Cladistic analysis, taxonomic revision & biological notes of the termitophilous genus Xenogaster Wasmann, 1891 (Staphylinidae, Aleocharinae, Corotocini)\" - Silva, Carlos Moreno Pires (2024)
Xenogaster Wasmann, 1891, is an exclusively Neotropical genus of termite-associated beetles, which are associated with termites of the genera Nasutitermes Dudley, 1890, and Cortaritermes Mathews, 1977. In this study, a cladistic analysis and taxonomic revision of the genus were conducted, which previously included 10 known species. The cladistic analysis encompassed 27 terminals (14 from the ingroup and 13 from the outgroup) and 135 morphological characters derived from an examination of both external and internal structures. The analysis, using implicit weighting, resulted in a more parsimonious phylogenetic tree with 419 steps. This topology supported the monophyly of the genus Xenogaster, with the support of 7 transformations, including two exclusive synapomorphies. Furthermore, two new species, Xenogaster utopica sp. nov. and X. rochai sp. nov., were identified based on morphological studies. A new genus, Paraxenogaster gen. nov., was established to accommodate a species previously described in the genus Xenogaster, and the new combination Paraxenogaster fossulata comb. nov. was proposed. Additionally, the cladistic analysis revealed that the species Xenogaster mexicana Kistner & Jacobson, 1976 belongs to the genus Trachopeplus Mann, 1923, resulting in the new combination T. mexicanus comb. nov.. Both genera, Xenogaster and Paraxenogaster, along with the 13 species, were thoroughly described or redescribed, illustrated, and identification keys for the genus Xenogaster and the Neotropical genera of the subtribe Termitogastrina, to which Xenogaster belongs, were provided. Furthermore, the phenomenon of post-imaginal growth in Xenogaster was discussed based on specimens collected at several stages of development of physogastry.